Single-cell RNA-seq reveals cellular heterogeneity from deep fascia in patients with acute compartment syndrome - Wang, Tao; Long, Yubin; Ma, Lijie; Dong, Qi; Li, Yiran; Guo, Junfei; Jin, Lin; Di, Luqin; Zhang, Yingze; Wang, Ling; Hou, Zhiyong (Frontiers in Immunology, 2023)
Introduction High stress in the compartment surrounded by the deep fascia can cause acute compartment syndrome (ACS) that may result in necrosis of the limbs. The study aims to investigate the cellular heterogeneity of the deep fascia in ACS patients by single-cell RNA sequencing (scRNA-seq). Methods We collected deep fascia samples from patients with ACS (high-stress group, HG, n=3) and patients receiving thigh amputation due to osteosarcoma (normal-stress group, NG, n=3). We utilized ultrasound and scanning electron microscopy to observe the morphologic change of the deep fascia, used multiplex staining and multispectral imaging to explore immune cell infiltration, and applied scRNA-seq to investigate the cellular heterogeneity of the deep fascia and to identify differentially expressed genes. Results Notably, we identified GZMK+interferon-act CD4 central memory T cells as a specific high-stress compartment subcluster expressing interferon-related genes. Additionally, the changes in the proportions of inflammation-related subclusters, such as the increased proportion of M2 macrophages and decreased proportion of M1 macrophages, may play crucial roles in the balance of pro-inflammatory and anti-inflammatory in the development of ACS. Furthermore, we found that heat shock protein genes were highly expressed but metal ion-related genes (S100 family and metallothionein family) were down-regulated in various subpopulations under high stress. Conclusions We identified a high stress-specific subcluster and variations in immune cells and fibroblast subclusters, as well as their differentially expressed genes, in ACS patients. Our findings reveal the functions of the deep fascia in the pathophysiology of ACS, providing new approaches for its treatment and prevention.